Chemical Composition of Mealworm Larvae (Tenebrio molitor) Reared in Serbia - Jajić Igor (Contemporary Agriculture, 2019)
The use of insects as “novel” and natural feed materials seems to be an attractive alternative protein source for poultry, pigs and fish since more than 80% of their chemical composition (dry weight basis) is crude protein and crude fat content. Therefore, the aim of this study was to determine some chemical composition parameters of powdered mealworm larvae, as a potential animal feed as well as human novel food. It was found that the crude protein (55.83%) and crude fat (25.19%) content was predominant, as well as that the content of nitrogen-free extract was low. Coincided with the high protein content, the levels of the most important amino acids were found to be considerable, especially lysine (3.18%) and threonine (1.34%). Crude fibre content was 7.15%, while ash was 4.84%. The samples were found to be rich in most nutritive elements, especially phosphorus (1.06%) and potassium (1.12%) in terms of macroelements, and zinc (138.2 mg/kg) in terms of microelements. Based on our research and other experimental results, it can be concluded that meals from the insects originating from the order Coleoptera, Tenebrionidae (mealworms) may be successfully used as feed material in diets of livestock animals, especially poultry.